Diagnostic and Therapeutic Indications for Endoscopic Ultrasound (EUS) in Patients with Pancreatic and Biliary Disease—Novel Interventional Procedures - Manfred Prager; Elfi Prager; Christian Sebesta; Christian Sebesta (Current Oncology, 2022)
There is growing evidence supporting the substantial, essential and indispensable role of endoscopic ultrasound (EUS) as a key diagnostic armamentarium for upper GI oncologic surgery. Well described in countless publications, EUS holds that position in gastroenterological expert centers all over Europe. Despite its undisputable contributions to oncologic upper GI surgery, the availability of this technique at the expert level shows up in an irregular spread pattern. Endoscopic ultrasound’s primary use during the first few years after its creation was the detection of pancreatic cancer. From then on, EUS developed in different directions, becoming a diagnostic tool that increasingly better defines its status as a method of minimally invasive therapeutic applications and a useful addition to surgical options. As a result, several surgical interventions could even be replaced by ultrasound-targeted interventions. This process took place in just a few years and was made possible by technical development that sensibly combined high-resolution ultrasound with therapeutic endoscopy. The present article will serve to cover the most prevalent uses with supporting data considering the growing list of suggested indications for EUS while also examining cutting-edge initiatives that might soon become the standard of clinical practice. Endoscopic centers with high expertise are needed to train future experts in the growing field of EUS interventions.